Perceived triggers of asthma impair quality of life in children with asthma. Issue 7 (14th May 2019) - Kansen, Hannah M.; Le, Thuy‐My; Meijer, Yolanda; Uiterwaal, Cuno S. P. M.; Knulst, André C.; van der Ent, Cornelis K.; van Erp, Francine C.
Abstract: Background: Data on the impact of the number and nature of perceived asthma triggers on health‐related quality of life (HRQL) in children are scarce. Objective: To investigate the impact of perceived asthma triggers on both asthma‐specific and generic HRQL in children. Methods: A cross‐sectional study was conducted among children (7‐18 years) with asthma in secondary and tertiary care. Children were screened with electronic questionnaires regarding respiratory and allergic symptoms. Asthma‐specific HRQL was assessed using the Pediatric Asthma Quality of Life Questionnaire (PAQLQ) (score range 1‐7) and generic HRQL using the RAND questionnaire (score range 7‐32). The Kruskal‐Wallis test and one‐way ANOVA were used to test the difference of, respectively, the PAQLQ and RAND scores across the number of perceived asthma triggers (0, 1‐2, 3‐4, or ≥ 5). Univariable and multivariable linear regression analyses were performed to evaluate the association between individual triggers and HRQL. Results: A total of 527 children with a mean (SD) age of 12.1 (2.9) years were included. Children with a higher number of perceived triggers had significantly lower PAQLQ and RAND scores (ie poorer HRQL). The difference in PAQLQ scores was clinically relevant between children with 0 versus 3‐4 or ≥ 5 triggers and 1‐2 versus ≥ 5 triggers (mean difference 0.66, 1.02 and 0.63, respectively). Especially, non‐allergic triggers (physical exercise, the weather, (cigarette) smoke and emotions) were significantly associated with reduced PAQLQ scores. Emotions and food/drinks were associated with reduced RAND scores. Conclusion and Clinical Relevance: A higher number of perceived triggers of asthma were associated with reduced HRQL in children with asthma. Especially, non‐allergic triggers were associated with reduced HRQL.